The Application of Qualitative Research in the Field of Nursing - Hou Yongmei (Scientific Research, New Technologies and Applications Vol. 10, 2024)
Background: With the expansion and deepening of nursing research and the strengthening of the concept of "patient-centered", the application of qualitative research in the field of nursing is becoming increasingly widespread, expanding the width and depth of nursing research and improving the effectiveness of nursing work. However, there are some shortcomings. Objective: Taking phenomenological method, Grounded Theory, ethnographic research, and narrative research as examples, this article aims to analyze the status and shortcomings of qualitative research in nursing, and provide a reference for subsequent research. Methods: Retrieve nursing qualitative research literature from China National Knowledge Infrastructure (CNKI), Pubmed, PsycINFO, and EMBASE, state the basic concepts of qualitative research, analyze the development process and trends, research hotspots, and shortcomings of nursing qualitative research. Results: A total of 52 articles were included, and nursing qualitative research has flourished. The research fields have shown a trend of diversification, and the overall number of publications has been increasing year by year. The target population of the research is becoming increasingly diverse, the scope of the explored topics is becoming wider, and the research methods are becoming more diverse. Conclusion: Qualitative research in nursing is still in the development stage. In the future, cooperation among multiple institutions and research on influencing factors can be strengthened to explore the underlying reasons for patient experiences and provide a basis for improving these experiences.